Synergetics of hypnoid relaxation - (:unkn) unknown (GEORG THIEME VERLAG KG, 2004)
The Autogenic Training (AT) is a well established relaxation technique and psychotherapy tool. We report the use of nonlinear routines, the Multi-scaled Time-Frequency-Distribution (mTFD) for the graphical display of vegetative rhythms, and Post-Event-Scan (PES) for the direct visual identification of coupling between physiological subsystems. Applying these methods to time series of respiration, arterial blood pressure, and cutaneous forehead blood content fluctuations in controls (n = I I) or AT-experts (ATE, n = 11) induced psychomotor drive reduction during orthostatic stress allowed the instantaneous identification of a 0.15 Hz-rhythm. This rhythm prevailed in ATE significantly longer resulting a significantly robust 1 : 1 coupling between cutaneous blood content fluctuations and respiration. Consequently, we hypothesize that the ,,0.15 Hz-rhythm in the cutaneous blood content fluctuations described previously which was associated with the subjective experience of profound psychomotor relaxation reflects an order-order transition in peripheral signals of central nervous origin. Results produced with the aid of these analytic tools support the efficacy of the AT induced, synergetic relaxation response.
Keywords: hypnoid relaxation; synergetics; nonlinear analysis; vegetative rhythms; n : m phase synchronization; dynamic systems; CLIENT-THERAPIST INTERACTION; HEART-RATE-VARIABILITY; SKIN BLOOD-FLOW; CHAOTIC PROCESS; LASER-DOPPLER; TIME-SERIES; PSYCHOTHERAPY; TRANSITIONS; RESPONSES; STATES